Personalized medicine and genome-based treatments: Why personalized medicine ≠ individualized treatments. (December 2014) - Nicholls, SG; Wilson, BJ; Castle, D; Etchegary, H; Carroll, JC
The sequencing of the human genome and decreasing costs of sequencing technology have led to the notion of 'personalized medicine'. This has been taken by some authors to indicate that personalized medicine will provide individualized treatments solely based on one's DNA sequence. We argue this is overly optimistic and misconstrues the notion of personalization. Such interpretations fail to account for economic, policy and structural constraints on the delivery of healthcare. Furthermore, notions of individualization based on genomic data potentially take us down the road of genetic reductionism obscuring the role of environmental factors in disease and ill health. We propose that one should see personalized medicine as a way of using personal genomic information to stratify individuals into subpopulations and suggest that personalized medicine be seen within a broader idea of personalized healthcare, reflecting healthcare that integrates personal genomic data into cultural, environmental and personal contexts.